Interventional Neuroradiology of the Spine Clinical Features, Diagnosis and Therapy - Muto, Mario; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2013)
Accurate interpretation of indications for treatment is the cornerstone of success in medicine. This book carefully examines the relation between clinical features, diagnosis, and choice of minimally invasive technique for a range of spine pathologies. It explains how selection of technique is intimately related to clinical and diagnostic aspects and how recognition of this relation forms the foundation for an optimal outcome. In addition to examining the various minimally invasive options, including the latest techniques, careful attention is paid to the role of medical treatment in avoiding recurrence after initial therapy. Nerve blocks, epidural injections, and intradiscal procedures are among the many options available in the armamentarium of the interventionalist, and advice is given on their use in different contexts. This volume will be of great value for neuroradiologists and others responsible for treating patients with spine disorders.
1 Biomechanics of the Spine and the Etiopathogenesis of Spinal Pain -- 2 Diagnostic approaches to spinal disease related to spinal intervention -- 3 Radiological Anatomy and Approaches to the Spine -- 4 Clinical Evaluation of Spinal Disease -- 5 How and When to Carry Out Spinal Biopsy -- 6 Percutaneous Treatment of Cervical and Lumbar Disks -- 7 Treatment of Facet Joints -- 8 Epidural and Sacral Spinal Injections -- 9 Vertebroplasty in Porotic Fractures -- 10 Medical Therapy in Porotic Patients -- 11 Vertebroplasty and Spinal Tumors -- 12 Kyphoplasty and Kyphoplasty-like Devices: Indications and Results -- 13 Endoscopic Treatment Approaches to Herniated Lumbar Disks -- 14 Percutaneous Lumbar Posterior Stabilization for Low Back Pain -- 15 New Treatments for Spinal Tumors -- 16 Indications and Results for Minimally Invasive Spinal Surgery -- 17 Radiotherapy for the Treatment of Bone Metastases -- 18 Classification and Treatment of Vascular Malformations of the Spinal Cord -- 19 Practical Guidelines for Percutaneous Vertebral Cementoplasty.
Keywords: Medicine; Radiology, Medical; Interventional radiology; Neurosurgery; Orthopedics; Medicine & Public Health; Imaging / Radiology; Interventional Radiology; Neuroradiology; Neurosurgery; Orthopedics